SEDIMENTARY EVOLUTION OF A PALAEOZOIC BASIN AND RIDGE SYSTEM: THE MIDDLE AND UPPER DEVONIAN OF THE AHNET AND MOUYDIR (ALGERIAN SAHARA) - Wendt J.; Kaufmann B.; Belka Z.; Klug Ch.; Lubeseder S. (My University, 2006)
The Ahnet and Mouydir regions of southern Algeria are part of one of the world's largest, almost undeformed exposures of Palaeozoic rocks which exemplify a hitherto poorly known early Variscan development of a Devonian basin and ridge system. This area includes a series of intracratonic basins along the northern margin of the West African Craton which consists (from W to E) of the Reggane Basin, Azel Matti Ridge, Ahnet Basin, Foum Belrem Ridge and Mouydir Basin. The depositional and palaeogeographic interpretation is based on 71 sections in this region, which for the first time were biostratigraphically calibrated by means of conodonts, goniatites and brachiopods. The structural evolution during Devonian times was probably controlled by reactivation of ancient N-S- to NW-SE-running faults in the Precambrian basement, which caused differential subsidence and uplift of a previously largely unstructured siliciclastic shelf. A hiatus during Emsian times indicates widespread emergence during this interval. The entire area was flooded during the earliest Eifelian, when the first vestiges of the Azel Matti Ridge become evident by stratigraphic condensation. The palaeogeographic differentiation is most apparent during the Givetian, when a shoal with reduced carbonate sedimentation was established on the Azel Matti Ridge passing towards the west and east into basinal environments of the Reggane and Ahnet basins, respectively. The Foum Belrem Ridge is distinguished by increased subsidence during the early Givetian and by revived uplift during the late Givetian. In the Mouydir Basin further east, up to 1000 m of shales were deposited during the Givetian. The early Frasnian is marked by the ubiquitous sedimentation of black shales and bituminous styliolinites. These lithologies occur repeatedly already during the Middle Devonian and document intermittent anoxic conditions. The basin and ridge topography is levelled by the shallowing-up sequence of up to 1400 m thick upper Frasnian and Famennian shales which grade into a deltaic sequence of uppermost Famennian/Tournaisian sandstones. The up to now only vaguely discriminated lithostratigraphic formations of the Devonian have been biostratigraphically defined in suitable type sections.
Keywords: DEVONIAN; BIOSTRATIGRAPHY; PALAEOGEOGRAPHY; BASIN EVOLUTION; ALGERIAN SAHARA; Палеозой::Девонская; Paleozoic::Devonian